Indonesia Vs China: A Comparative Of The Execution Of Death Penalty In Corruption - Ony Rafsanjani (Fakultas Hukum Universitas Mataram, 2022)
Indonesia and China are some of the countries that still adhere to the death penalty in their Criminal Code. One of the crimes punishable by death is the Corruption Crime because it is considered an extraordinary crime and is believed to reduce crime rates. This research examines material differences regarding the death penalty law, especially in cases of corruption in Indonesia and China. The type of research used in this research is normative or doctrinal research with statutory, conceptual, and legal comparative approaches. Sources and types of legal materials consist of primary, secondary, and tertiary legal materials. Primary legal materials are in the form of legislation, secondary legal materials in the form of expert opinions, previous research, text books, scientific journals, and news on the internet, while tertiary legal materials include Indonesian language dictionaries, English dictionaries, and legal dictionaries. The results of this study reveal that there are differences and similarities in determining the death penalty for the crime of corruption for corruptors between Indonesia and China. The similarities are that they both assume that corruption is a crime that can be sentenced to death and has a special institution in handling it. The difference lies in the regulation, if in Indonesia the crime of corruption is regulated in a special law (outside the Criminal Code) while in China it is regulated in their Criminal Code. A further difference lies in the additional penalties where China has a political disenfranchisement. Regarding the implementation of the death penalty for corruptors, in Indonesia it applies if certain things occur (disasters and monetary crises) in China, calculated based on the amount of corruption. Meanwhile, according to the method of execution, in Indonesia it uses shooting to death, in China it uses shooting and death injections.